First characterization of seagrasses at Sámara Bay, Pacific coast of Costa Rica - Samper Villarreal, Jimena (2022)
Seagrasses are found at limited locations in the Eastern Tropical Pacific (ETP). Here, we provide the first characterization of seagrasses at Sámara Bay, on the northern Pacific coast of Costa Rica. Sampling was carried out in August 2018 and March 2019. We measured seagrass biomass, shoot density, leaf area, stable isotope composition (δ13C, δ15N), carbon content, bulk density, and grain size. We also measured water clarity, temperature, dissolved oxygen, salinity, and nutrient concentrations. Two seagrass species were found, Halophila baillonii and Halodule beaudettei, which are commonly found in the ETP. Sediment grain size at Sámara was mostly composed of fine and very fine sand. Total seagrass biomass was 31.9 ± 28.7 g DW m−2 and density was 2136 ± 1576 shoots m−2. Halophila bailloni leaf blade length (1.1 ± 0.3 cm) and width (0.5 ± 0.1 cm) were within ranges for the sizes reported for this species, and were similar to other locations. Halodule beaudettei leaf length (5.0 ± 3.8 cm) and width (0.09 ± 0.02 cm), were larger than at other seagrass meadows on the Pacific coast of Costa Rica yet smaller than in Brazil. Seagrass biomass and density at Sámara were higher in the sampling during the dry season, a pattern also found on the Pacific coast of Costa Rica and in Brazil. We recommend further study of seagrasses at this site and the ETP, including temporal and spatial variability and associated environmental factors. Seagrass presence at Sámara should be considered in local management and conservation initiatives.